Numerical Study of 500 KHz Electromagnetic Wave Irradiation for Root Canal Sterilization in Apical Periodontitis Treatment - Srianant, Yanakorn; Tiengthong, Thanadol; Tarao, Hiroo; Akutagawa, Masatake; Yumoto, Hiromichi; Tominaga, Toshihiko (My University, 2025)
Periodontitis, a primary cause of inflammation and tooth loss, can be treated by inserting an electrode into the root canal and applying a 500 kHz current for sterilization through Joule heat. However, achieving sufficient temperature rise to sterilize bacteria remains challenging for teeth with an isthmus, indicating a need for further research. Numeral results show that the temperature significantly exceeds 60° C around the active electrode and between the active electrode and the ground electrode, with a particular temperature rising when the ground electrode is positioned inside the root canal. These findings highlight the need for further research to optimize treatment efficiency, particularly in improving temperature control and sterilization effectiveness.
Keywords: coupled analysis; electric current flow; isthmus root canal; periodontitis; temperature distribution